The Seroprevalence of CMV in Women with Bad Obstetric History in Babil/Iraq - Abbas, Maha Diekan; Egbe, Solomon Sahoon (Iraqi Journal of Pharmaceutical Sciences, 2021)
Placental dysfunction and or fetal central nervous system infestation caused by Human cytomegalovirus (HCMV) is the leading cause of congenital non-genetic neuro-developmental problems of the newborn, worldwide. Although the highest rates of congenital infection and CMV seroprevalence occurs in developing countries like Iraq, there remains a paucity of data from that part of the world. This descriptive case control study was undertaken in Babylon/ Iraq to determine the local seroprevalence of CMV in women of child bearing age, and to identify the socio-demographic factors associated with it. This study found a seropositivity peak amongst the 26-35 yr olds which declined in the 36 – 45 yr olds. However, the evidence of current infection was stable at 25% among the 26-35 yr olds and the 36 – 45 yr old women. Overall seropositivity was at 77.32%, a susceptibility rate was at 22.68%, and seropositivity for IgG was highest among the educated, those living in overcrowded settings, and those with poor obstetric histories. Our study concludes that CMV screening of women in the Al Hamza district in Babylon/Iraq and the availability of advice on how to prevent the infection can be beneficial for health outcomes.